Optic nerve neuropathies – causative factors, methods of diagnostics, current and future possibilities of treatment - Kobak, Joanna; Tyczyńska, Magdalena; Forma, Alicja; Dudek, Iga; Maani, Amr; Zembala, Patryk; Baj, Jacek (Journal of Education, Health and Sport, 2022)
Introduction: Optic neuropathies are a broad group of diseases in which the dominant disturbance is damage to the optic nerve, often irreversible. Underlying causes of neuropathy are both genetic and environmental. Despite limited treatment options, much research is currently being done on substances that could improve optic nerve function and alleviate the clinical consequences of optic nerve damage. Purpose: This article describes current findings in both the optic nerve neuropathy pathophysiology and diagnosis of the disorder, as well as treatment options and future perspectives. State of knowledge: The pathogenetic cause of neuropathy is mainly demyelination within the neural sheath, often caused by inflammation. It is characterized by progressive loss of vision. The most common genetic cause of optic neuropathy is mitochondrially inherited Leber hereditary optic neuropathy (LHON) and is characterized by mostly sudden and painless loss of visual acuity. Toxic neuropathies are a group of diseases caused by heavy metals, pharmaceuticals, methanol and carbon monoxide. Nutritional neuropathy is mainly related to vitamin B1, B9 and B12 deficiency, and is a rare example of neuropathy that can be curable at the early stage of the disease. Another group of neuropathies is caused by ischemia and can be divided according to the place of the optic nerve affected – AION (anterior ischemic optic neuropathy) and PION (posterior ischemic optic neuropathy). Conclusions: The therapeutic options in the treatment of optic neuropathy strictly depend on the causative factor. Nutritional deficiencies are treated with appropriate supplementation, so it is vital to truly determine the missing vitamins and elements.